Better the Last Known Domicile (in the EU) than an Unknown One: The Determination of International Jurisdiction in a Contract Concluded with a Consumer, Regarding the CJEU Judgment of 11 April 2024, Credit Agricole Bank Polska, C-183/23 - Mariscal González, Ada Lucía (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
The CJEU Judgment of 11 April 2024 in Credit Agricole Bank Polska (C-183/23) examines key aspects regarding the determination of international jurisdiction in consumer contracts under the Brussels I Bis Regulation. The ruling reaffirms that, in the absence of conclusive evidence regarding the consumer’s current domicile, the last known domicile within the EU serves as the decisive criterionfor establishing jurisdiction, aimed at safeguarding the consumer’s procedural rights. The referring court also raises the question of whether the appearance of a judicially appointed representative, designated under national procedural law, constitutes tacit submission by the consumer if no objection to jurisdiction has been raised. The CJEU considers this issue to be residual, as jurisdiction is already determined pursuant to Article 18.2 of the Brussels I Bis Regulation. Furthermore, the Court underscores the irrele-vance of the defendant’s nationality in determining international jurisdiction in consumer contract cases.
Keywords: Jurisdiction; Contract Concluded with a Consumer; Unknown Domicile; Last Known Domicile; Brussels I Bis Regulation